C26 COMPLETE REVASCULARISATION IMPROVES SURVIVAL OF PATIENTS RESUSCITATED AFTER AN OUT–OF–HOSPITAL CARDIAC ARREST. (18th May 2022) - Kajana, V; Primi, R; Gentile, F; Compagnoni, S; Baldi, E; Mandurino Mirizzi, A; Repetto, A; Ferrario, M; Ferlini, M; Marinoni, B; Bendotti, S; Currao, A; et al.
Abstract: Background: Sudden cardiac death is a major issue in industrialised countries and survival of patients after out–of–hospital cardiac arrest (OHCA) remains low. Acute myocardial infarction (AMI) is the principal cause of OHCA and myocardial revascularisation plays a positive role on survival. In this setting little is known about the role of complete (CR) versus culprit–only revascularisation (IR) on survival. Purpose: The aim of this study was to assess whether CR could lead to a better one–year survival as compared to IR. Methods. Among patients prospectively enrolled in the Lombardia CARe OHCA registry from January 1 2015 to May 1 2021, who underwent a coronary angiography (CAG) at the Fondazione IRCCS Policlinico San Matteo were enrolled in this study. CAGs were retrospectively reviewed by two interventional cardiologists. Prehospital and survival data were retrieved from the registry. Results: We enrolled 239 patients [mean age 63.7±12.4 years; male 79.9%; shockable presenting rhythm 84.1%; AMI at post ROSC ECG 67.9%; ejection fraction 37% (30–45), circulatory support with ECMO 10.9%]. Among the 119 (50%) patients with multi–vessel disease, 82 (69%) received IR whereas 37 (31%) received CR [8 during the first procedure, 29 in a second procedure with a median time after OHCA of 5 (2.5–10) days]. This latter group showed significantly higher one–year survival (54.9% vs 16.2%, p < 0.001). At univariable logistic regression only a shockable presenting rhythm and the presence of chronic total occlusion (CTO) were significantly associated with the probability of receiving a CR [OR 5.1 (95%CI 1.1–22), p = 0.03; OR 0.37 (95%CI 0.16–0.85), p = 0.02 respectively]. However, at multivariable regression analysis only CTO was significantly associated with the probability of receiving a CR [OR 0.36 (95%CI 0.15–0.9), p = 0.007]. At Cox multivariable regression model cardiac arrest duration (longer that the median value of 24 min) and CR were independently associated with the probability of death [HR 3.6 (95%CI 1.9–6.9), p < 0.001; HR 0.2 (95%CI 0.1–0.9), p = 0.02]. Similarly, cardiac arrest duration, CR and a shockable presenting rhythm were associated with the probability of death or poor neurologic outcome [HR 3.3 (95%CI 1.8–6), p < 0.001; HR 0.5 (95%CI 0.3–0.9), p = 0.03 and HR 0.2 (95%CI 0.1–0.5), p < 0.001]. Conclusions: Complete revascularisation is independently associated with a better one–year survival in patients resuscitated from an out–of–hospital cardiac arrest.